Benchmark of the Oxford Nanopore, EM-seq, and HumanMethylationEPIC BeadChip for the detection of the 5mC sites in cancer and normal samples - Deinichenko, Kseniia A.; Vynogradskaya, Valentina G.; Grebnev, Pavel A.; Mikova, Valeriya M.; Bobylev, Dmitriy O.; Shaymardanov, Abusaid M.; Ivashechkin, Alexey A.; Erokhina, Marina V.; Akinshina, Alexandra I.; Semyanihina, Anna V.; Mitrofanov, Sergey I.; Grammatikati, Konstantin S.; et al. (Frontiers in Epigenetics and Epigenomics, 2024)
Whole genome DNA methylation identification is crucial for profiling of the physiologically and clinically relevant epigenetic changes. Although there are multiple experimental methods, their accuracy, advantages and disadvantages need to be investigated in application to the complex tissue objects. Here we performed a benchmark of 5mC detection with Oxford Nanopore and EM-seq methods. To this end, we profiled in a genome wide manner 5mC sites in colorectal tumors and normal tissues for 3 patients and applied HumanMethylationEPIC BeadChip as an additional control approach. We estimated the whole genome scale of the methylation detection that each method yields. Our investigation describes sensitivity and specificity of each platform and impact that sequencing coverage brings. From our analysis follows higher sensitivity and specificity of the Nanopore sequencing over the EM-seq method. Moreover, ONT sequencing followed by Megalodon methylation detection demonstrates better quantitative agreement of the epigenetic signals between biological replicates. Also, our analysis highlights that with 40X and above coverage EM-seq slightly outperforms ONT and yields high accurate detection of the 5mC signals (AuPR=0.99178, AuROC=0.98161). The study has been performed for colon cancer and 1 Deinichenko et al.